Estimation of the Bid-Ask Prices for the European Discrete Geometric Average and Arithmetic Average Asian Options - Xiankang Luo; Tao Chen (Discrete Dynamics in Nature and Society)
Conic finance is a new and exciting development in quantitative finance, which is widely applied to several topics in finance. The theory of conic finance extends the law of one price to the law of two prices, which yields closed forms for bid-ask prices of European options. In this paper, within the framework of conic finance, we derive effective, explicit, approximate formulas to estimate the bid-ask prices for the European discrete geometric average and arithmetic average Asian options. Finally, we give two examples to demonstrate and validate that the approximate closed-form solutions are efficient and accurate.